Application Of Quality Function Deployment (QFD) Method In Developing Eco-Friendly Cup Holder Design - Rani Azizi Alatas; Alesa Putri; Tono Subroto (Jurnal Riset Ilmu Teknik, 2025)
The rapid growth of Indonesia’s food and beverage industry has increased the need for innovative and environmentally friendly packaging, especially for takeaway drinks. This study aims to develop a cup holder design to replace plastic bags by integrating customer needs using the Quality Function Deployment (QFD) method. QFD was chosen because it can translate the Voice of Customer (VoC) into measurable technical specifications through the House of Quality (HoQ) matrix. The research used a descriptive quantitative approach with 30 café customers selected through purposive sampling. Validity testing using the Pearson Product Moment showed that 11 out of 20 statements were valid (r > 0.36), and the reliability test achieved a Cronbach’s Alpha value of 0.870, indicating high consistency. The results of the VoC and HoQ analysis identified eleven important customer needs such as capacity, ease of use, material strength, design, and price efficiency. Three alternative cup holder designs were evaluated using the Pugh Matrix, and the best concept scored +4, featuring a kraft paper material with 300 gsm thickness, moisture resistance, ergonomic shape, and the ability to hold four cups while displaying café branding. This design improves customer comfort, strengthens brand image, and reduces plastic waste. The study demonstrates how QFD can effectively link customer preferences to engineering design, offering a practical example for small and medium cafés to develop sustainable packaging that supports both product functionality and environmental responsibility.